Stability of the blood lactate-heart rate relationship in competitive athletes - Forster, C.; Fitzgerald, D. J.; Spatz, P. (Medicine & Science in Sports & Exercise, 1999)
Although power output at AerT (aerobic threshold), AnT (anaerobic threshold), and maximal exercise changes significantly with conditioning, there is no systematic change in the associated values for HR and/or RPE used as practical markers of training intensity. Accordingly, a single well-conducted evaluation may allow evaluation of appropriate training markers that may be longitudinally stable.